ByzRev 08.2026.001: Alasdair C. Grant, Greek Captives and Mediterranean Slavery, 1260–1460: (Edinburgh Byzantine Studies). Edinburgh: Edinburgh University Press 2024. - Schiel, Juliane (The Byzantine Review, 2026)
Alasdair C. Grant, Greek Captives and Mediterranean Slavery, 1260–1460 (Edinburgh Byzantine Studies). Edinburgh: Edinburgh University Press 2024. 256 S. – ISBN 978-1-399523-83-7